PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, KEPERCAYAAN, HARGA, DAN DAYA TARIK PROMOSI, TERHADAP INTENSI PENGGUNAAN E-WALLET SHOPEEPAY SEBAGAI SISTEM PEMBAYARAN DIGITAL PADA GENERASI Z DI KOTA SEMARANG - Alifia, Fariska Desma; Kusuma, Septian Yudha; Prihatiningsih, Prihatiningsih (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyse the significance of the effect of perceived ease of use, trust, price and promotional attractiveness on the intention to use the ShopeePay e-wallet as a digital payment system for Generation Z in Semarang City. The population in this study were generation z in Semarang City who used the ShopeePay e-wallet. The data in this study were taken using non-probability sampling techniques with incidential sampling methods, as many as 120 respondents. The data analysis model uses a Multiple Linear Analysis Model. While data analysis techniques use the F Test, the Coefficient of Determination Test (R2), and the t statistical test. The results of this study partially show that promotional attractiveness, price, and perceived ease of use have a significant effect on the intention to use the ShopeePay e-wallet as a digital payment system for generation z in the city of Semarang. However, partially trust has an insignificant effect on the intention to use the ShopeePay e-wallet as a digital payment system for generation z in the city of Semarang